(untitled) (ModaPalavra e-periódico, 2008)
The term production chain express the textile system and of confection that if configures as one filière, governed for the purchaser and characterized for raised degree of complement, on which depends good part of the success that the product gets in the market. Embody diverse productive sectors, since the manufacturing activities of base until the advanced services of distribution, which present certain peculiarities, such as: structural and technological diversity; productive segmentation; sub contraction relations; bifurcation between the productive activities (materials) and the corporate functions (abstract). Currently, it crosses a phase of great changes in the face of the globalization process the emergence of new markets. The most sensitive components of such changes are the relocation of production due to operational costs; the exasperation of competition, the reduction of the life cycle of fashion products; the fast increment of technologies and complex structural changes of the markets. The study of this new world-wide conjuncture is essential for the creation of pro-competitive actions which base themselves on a dynamic group of elements that assure the attainment of solid comparative advantages towards the new market demands.